Involvement of Hemopexin in the Pathogenesis of Proteinuria in Children with Idiopathic Nephrotic Syndrome - Pukajło-Marczyk, Agnieszka (J Clin Med, 2021)
Hemopexin (Hpx) is considered a factor in the pathogenesis of idiopathic nephrotic syndrome (INS). The aim of the study was to evaluate the serum and urine values of Hpx (sHpx and uHpx) in children with INS, analyze the role of Hpx, and assess its usefulness as a marker of the disease course. 51 children with INS and 18 age-matched controls were examined. Patients were divided into subgroups depending on the number of relapses (group IA—the first episode of INS, group IB—with relapses) and according to method of treatment (group IIA treated with gluco-corticosteroids (GCS), group IIB treated with GCS and other immunosuppressants). Hpx concentrations were determined by enzyme-linked immunosorbent assay (ELISA). sHpx and uHpx values in relapse were elevated in the whole INS group versus controls (p < 0.000). In remission their levels decreased, but still remained higher than in the control group (p < 0.000). In group IB uHpx levels were increased during remission as compared to group IA (p < 0.006). No significant impact of immuno-suppressants on sHpx was observed, but uHpx excretion in group IIA was higher in relapse (p < 0.026) and lower in remission (p < 0.0017) as compared to group IIB. The results suggest the role of Hpx in the pathogenesis of INS. Hpx may be a useful indicator for continuation of treatment, but it requires confirmation by further controlled studies.